Simultaneous extracorporeal liver and cardiorespiratory support with double plasma molecular absorption system and extracorporeal membrane oxygenation: A case report: DPMAS with ECMO - Thanapongsatorn, Peerapat; Krisem, Massupa; Wathanawanichakun, Sahaporn (Clinical Critical Care, 2025)
Introduction: Extracorporeal membrane oxygenation (ECMO) has emerged as a life-saving and bridging therapy for critically ill patients grappling with severe cardiopulmonary failure. However, ECMO is associated with multiple complications, including acute liver failure (ALF), which significantly worsens prognosis and mortality rates. This case report presents a unique instance of simultaneous extracorporeal liver and cardiorespiratory support. Case presentation: A 43-year-old female with a history of infective endocarditis and prior Bentall’s operation, who developed acute decompensated heart failure and cardiogenic shock due to a pseudoaneurysm compressing the left main coronary artery. She required high-dose vasopressors and was initiated on venoarterial ECMO (VA-ECMO) for circulatory and respiratory support. However, her condition worsened with the onset of hepatic encephalopathy and severe hyperbilirubinemia, indicative of acute liver failure, likely due to ischemic hepatitis, congestive hepatopathy, and ECMO-related hemolysis. To address her worsening hepatic dysfunction, we initiated the double plasma molecular absorption system (DPMAS) for three consecutive sessions as a bridge to definitive surgical repair. This intervention led to improvements in hepatic and renal function, allowing for successful ECMO weaning after 10 days. Three days after ECMO discontinuation, she underwent pseudoaneurysm repair and was subsequently discharged in stable condition. Conclusions: To the best of our knowledge, this simultaneous management of acute liver failure and acute cardiorespiratory failure has never been reported in the literature. Our approach effectively reduced hyperbilirubinemia, improved hepatic encephalopathy, and facilitated successful bridging to cardiac surgery.